Penguatan Literasi, Numerasi, dan Adaptasi Teknologi melalui Program Kampus Mengajar di SD Negeri Inpres 21 Sowi - Revisika Revisika; Fitri Armiati; Dian Indriyani; Dwi Septipane; Gunawan Gunawan (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
Basic education in peripheral areas continues to face various challenges, particularly in terms of literacy, numeracy, and the utilization of learning technologies (Pratiwi, 2021; OECD, 2019). SD Impres 21 Sowi in Manokwari Regency is one of the elementary schools experiencing limited resources, low student reading interest, and minimal use of technology-based learning media (Direktorat Sekolah Dasar, 2020; Nugroho & Prasetyo, 2022). The Kampus Mengajar program is part of the Merdeka Belajar policy, which involves university students in contributing directly to the improvement of basic education quality (Kemendikbud, 2020; Kemendikbudristek, 2021). This community service activity aims to strengthen the role of university students in supporting the learning process through literacy and numeracy assistance as well as technology adaptation at SD Impres 21 Sowi. The implementation method employs a participatory and collaborative approach through stages of observation, planning, implementation, and evaluation (Rahmawati & Susanto, 2020; Astuti & Lestari, 2022). The activities include reading and writing assistance, contextual numeracy learning, and the use of simple digital learning media (Widodo & Kadarwati, 2021; Nugroho & Prasetyo, 2022). The results indicate an increase in students’ learning interest, improvement in basic literacy and numeracy skills, and greater student engagement in the learning process. In addition, the program has a positive impact on strengthening the social and pedagogical competencies of university students (Yuliana & Hartono, 2022; Sutrisno & Widodo, 2022). The Kampus Mengajar program has proven to contribute positively to improving the quality of basic education, particularly in schools with limited facilities and infrastructure (Kemendikbudristek, 2022)